Aroma compositions and comparison of their related components of Longjing tea with different aroma types - ZHOU Senjie; HUANG Chuangsheng; LI Chunlin; GONG Shuying; GUO Haowei; TONG Yilin; FAN Fangyuan (浙江大学学报. 农业与生命科学版)
Longjing tea is a famous traditional tea in China and the aroma is an important factor in the quality evaluation of tea. In this study, Longjing tea samples were widely collected and explored by sensory evaluation, which dividing them into three aroma groups: tender aroma type, clean and refreshing aroma type, and approaching high aroma type. Then, simultaneous distillation extraction (SDE) and gas chromatography-mass spectrometry (GC-MS) were used for extraction and determination of aroma compositions. The result suggested that the aroma-characteristic compositions of Longjing tea with tender aroma, clean and refreshing aroma, and approaching high aroma, respectively, showed differences in types and relative contents of alcohols, aldehydes, terpenes, ketones, alkanes, alkenes, heterocycles, esters and so on. The results of principal component analysis (PCA) based on main aroma components showed that: 1) The contents of styrene, cetane, 3-methoxy-1, 2-propanediol were significantly and positively correlated with the tender aroma of Longjing tea; 2) the contents of (E)-β-farnesene, trans-4-tert-butylcyclohexanol and methyl jasmonate were significantly and positively correlated with the clean and refreshing aroma of Longjing tea; 3) the relative contents of phenylacetonitrile, acetophenone, 1, 3-cyclohexadiene-2, 2, 6-trimethyl-benzaldehyde were higher in Longjing tea with approaching high aroma. This study provides a theoretical basis for aroma description in sensory evaluation of Longjing tea.